Monitoramento e caracterização molecular de adenovírus humanos em amostras provenientes de pacientes submetidos ao transplante de células progenitoras hematopoiéticas - Santos, Hugo César Pereira (2015)
The human adenoviruses (HAdV) infect people of all ages worldwide, causing a wide range of clinical syndromes, depending on the viral type. In immunocompromised hosts, as transplanted patients, HAdV infection can result in a bad prognosis. Some aspects of viral pathogenesis, such as the association between viremia and/or viral load with disseminated disease and the optimal moment to start the therapy, are still not well established in adult patients that have undergone allogeneic hematopoietic stem cell transplantation (ASCT). Therefore, the main objective of this study was to monitor ASCT recipients for HAdV occurrence, and also correlate viral positivity, viral load and molecular variant with clinical symptoms and patients’ prognosis. For this, stool and serum from 21 patients were monitored in a 2 years period (from October/2012 to October/2014). Serum and fecal samples were screened by Nested-PCR, using primers targeting a partial region of the hexon gene (143bp). Fecal samples were further screened by a commercial enzyme immunoassay (EIA). In total, 57% of the patients had at least one positive sample (serum or stool) for HAdV. Patients presented high viral load (varying from 7,7x103 to 2x108 copies/mL), with a higher viral load in stool when compared to serum. Positive samples were submitted to genomic sequencing, revealing the occurrence of HAdV from C, D and F species. The main clinical symptom presented by infected patients was diarrhea, and graft-versus-host disease was the main intercurrence; however it was not possible to directly associate viral positivity to cause of death. We hope to contribute for a better understanding of the HAdV infection pattern in patients submitted to ASCT. Our data highlights the importance of the inclusion of HAdV testing in the routine laboratory exams of this group of patients.